THE EFFECT OF GUIDED-INQUIRY MODEL ON SCIENCE PROCESS SKILLS INDICATORS - Arinta Rezty Wijayaningputri; Wahono Widodo; Munasir Munasir (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
The aims of this research is to know the effect of Guided-Inquiry model on the indicators of science process skills, especially on Vibration and Waves Material. This research is done because of the importance of mastering indicators to identify the variables for students in experimenting. The research design which applied in this study was One-group Pre-test Post-test on 90 students of SMAN 1 Pasuruan. Data analysis technical using N-gain. For Class XI IPA 1 has an average N-Gain was 0,44. Ro Class XI IPA 2 has an average N-Gain was 0,47. Meanwhile for Class XI IPA 3 has an average N-Gain was 0,48. N-Gain was calculated based of pre-test and post-test results using the Science Process Skills Test, the results showed that there was a significant improvement of the students' science-process skill indicator for all three classes with N-gain score was 0.49. So, Guided-Inquiry model provide a good effect on the science process skill indicator on Vibration and Waves Material